Pesticides evaluation of environmental pollution - Rathore, Hamir Singh; Nollet, Leo M. L., 1948- (CRC Press, 2012)
"The extent and seriousness of the potential hazards due to pesticides still remains to be fully defined. This handbook discusses all aspects of pesticides residues in the environment. It presents current information on pesticide residues in humans, birds and mammals, fish, soil invertebrates, soil micro flora, aquatic invertebrate, surface and underground water, milk products, and more. It describes the degradation of pesticides in the atmosphere and in the environment. The text also covers the fate and transport of pesticides in the environment and the effects of pesticides on plants, animals, and humans. Other topics include biopesticides, biocides, and endocrine disrupting mechanisms"-- Provided by publisher.
Keywords: Pesticides -- Environmental aspects.; elektronické knihy; electronic books